Stability Constants of Mixed Ligand Complexes of Cu(II) and Ni(II) with Some Amino Acids and Phosphates - Aruna Adam; Suman Verma; Gita Seth (E-Journal of Chemistry)
The binary and ternary metal complexes of Cu(II) & Ni(II) with some amino acids (leucine, isoleucine & serine) as primary ligand and pyrophosphate (PP), adenosine-5´-triphosphate (ATP), as secondary ligand have been studied potentiometrically at 35 °C and a constant ionic strength (1.0 mol dm-3 KNO3). The formation of various binary and ternary complexes has been inferred from the corresponding titration curves. The Irving & Rossotti titration technique has been applied to determine the formation constants corresponding to various complexation equilibria.